2016
DOI: 10.18632/oncotarget.9733
|View full text |Cite
|
Sign up to set email alerts
|

JARID2 promotes invasion and metastasis of hepatocellular carcinoma by facilitating epithelial-mesenchymal transition through PTEN/AKT signaling

Abstract: JARID2 is crucial for maintenance of pluripotency and differentiation of embryonic stem cells. However, little is known about the role of JARID2 in metastasis of hepatocellular carcinoma (HCC). This study found that JARID2 expression was significantly higher in HCC tissues than that in adjacent non-tumor liver tissues (ANLTs), and its expression level correlated with HCC metastasis. High JARID2 expression was significantly correlated with multiple tumor nodules, high Edmondson-Steiner grade, microvascular inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
(72 reference statements)
3
28
0
Order By: Relevance
“…Previous studies have demonstrated that deficient migration and shallow invasion of trophoblasts may lead to preeclampsia (16,17). JARID2 has been suggested to regulate tumor cell migration and invasion; a previous study revealed that knockdown of JARID2 markedly inhibits hepatocellular carcinoma cell migration and invasion (13). Consistent with the results of this previous study, in the present study, it was observed that the knockdown of JARID2 significantly inhibited the viability and migration/invasion of HTR8/SVneo cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Previous studies have demonstrated that deficient migration and shallow invasion of trophoblasts may lead to preeclampsia (16,17). JARID2 has been suggested to regulate tumor cell migration and invasion; a previous study revealed that knockdown of JARID2 markedly inhibits hepatocellular carcinoma cell migration and invasion (13). Consistent with the results of this previous study, in the present study, it was observed that the knockdown of JARID2 significantly inhibited the viability and migration/invasion of HTR8/SVneo cells.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the suppression of PI3K/Akt signaling may be a promising approach for treating preeclampsia. A recent study reported that JARID2 promotes the activation of Akt in hepatocellular carcinoma (13). In the present study, it was observed that the knockdown of JARID2 suppressed the levels of phosphorylated PI3K and Akt in HTR8/SVneo cells.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The phenomenon known as epithelial-mesenchymal transition (EMT) promotes invasion and metastasis in many cancers [29][30][31], and we hypothesized that S1PR1 might be involved in EMT of GC cells. We treated MGC-803 cells with 10 ng/ml TGF-β1 for 24 hours.…”
Section: S1pr1 Expression Is Elevated In a Tgf-β1 Induced Emt Modelmentioning
confidence: 99%
“…The encoded protein is a DNA-binding protein that functions as a transcriptional repressor. It was reported to promote the invasion and metastasis of hepatocellular carcinoma by facilitating epithelialmesenchymal transition through the PTEN/AKT signaling pathways (Lei et al, 2016) and is essential for the maintenance of tumor-initiating cells in bladder cancer (Zhu et al, 2017). The protein encoded by CDK6 is a member of the CMGC family of serine/threonine protein kinases.…”
Section: Discussionmentioning
confidence: 99%